FAKTOR RISIKO GIZI KURANG PADA BALITA DI NUSA TENGGARA TIMUR - Kadek Dwi Ariesthi (CHMK HEALTH JOURNAL, 2019)
East Nusa Tenggara is the province with the prevalence of moderate and severe malnutrition second highest in Indonesia, amounting to 29,4%. The aim of this study was to identify the risk factors of moderate malnutrition in under-five children in East Nusa Tenggara. case control study was carried out from March to May 2014 in North Kodi sub-district, Southwest Sumba district, East Nusa Tenggara, consisted of 38 moderate malnutrition under-five children as cases and 76 healthy under-five children as controls. The risk factors studied were factors relating to the mother and child. Data were collected by conducting interviews of each respondent at their home. Bivariate analyses were performed to calculate the crude OR and multivariate analysis using logistic regression was conducted to calculate the adjusted OR. Bivariate analysis showed that family income (OR=15.2; 95%CI:5.2-43.9) and frequency of illness (OR=35.2; 95%CI:11.7-105.3) were the risk factors respectively. Multivariate analysis showed that the most significant risk factors were frequency of illness (OR=35.4; 95%CI:4.8 – 256.8), respectively. Frequency of illness were the predominant risk factors of moderate malnutrition in North Kodi sub-district, Southwest Sumba, East Nusa Tenggara. Keywords : moderate malnutrition in under five children, East Nusa Tenggara, case control